Progress in Upscaling Organic Photovoltaic Devices - Gabriel Bernardo (2021)
Organic photovoltaic (OPV) cells have recently undergone a rapid increase in power conversion efficiency (PCE) under AM1.5G conditions, as certified by the National Renewable Energy Laboratory (NREL), which have jumped from 11.5% in October 2017 to 18.2% in December 2020. However, the NREL certified PCE of large area OPV modules is still lagging far behind (11.7% in July 2020). Additionally, there has been a rapidly growing interest in the use of OPVs for dim light indoor applications, with reported PCE of some large area (≥1 cm2) devices, under 1000 lux, well above 20%. The transition of OPV from the lab to the market requires the development of effective manufacturing processes that can scale-up laboratory-scale devices into large area devices, without sacrificing performance and simultaneously minimizing associated manufacturing costs. This review article focuses on four important challenges that OPV technology has to face to achieve a reliable lab-to-fab transfer, namely: i) The upscaling of indium-tin-oxide (ITO)-based single cells and the interconnection of single cells into large area modules; ii) the development of alternatives to vacuum processing; iii) the development of alternatives to ITO-based substrates; and iv) strategies for improving the lifetime of large area OPV devices.